Thyroiditis â A Review - Begum, Afsana; Bari, Md Shafiqul; Ayaz, KFM; Yasmin, Rubina; Rajib, NC; Rashid, MA; Ahasan, HAM Nazmul; Siddiqui, FM (Journal of Medicine, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3329/jom.v7i2.1366 J MEDICINE 2006; 7 : 58-63